The Development of the Olympic Narrative in Chinese Elite Sport Discourse from Its First Successful Olympic Bid to the Post-Beijing Games Era. Issue 12 (12th August 2016) - Hu, Richard Xiaoqian; Henry, Ian
Abstract: As a phenomenon exogenous to China, the Olympics have been proactively interpreted in the local context since China's entry (and subsequent re-entry in 1984) into the Olympic movement. With China's increasing involvement in promoting three bids to host the Olympic Games, two of which were successful, respectively, in 2001 and 2015, the nature of the discourse of key stakeholders in relation to Chinese elite sport has both reflected and reshaped the meaning of the Games to Chinese elite sport. This paper examines the discursive construction process of the Olympics in the Chinese elite sport system by key stakeholders through analyzing statements of political figures on sport and Olympic phenomena, Chinese elite sport policy documents, and the commentaries of leading Chinese sport academics. The analysis of discourse highlights two main features in the construction of the Games in official accounts during the period under investigation. The development of these two themes reflects the nature of the Chinese Olympic discourse, manifests the political power over the interpretation of the Olympics in Chinese context, and continues to characterize the on-going major themes in Chinese elite sport policy.